Penganekaragaman Bahan Pangan Sebagai Strategi Mempertahankan Daya Tahan Tubuh Di Masa Pandemi Covid-10 - Widyaningrum, Bakti; Helbawanti, Octaviana; Khoerunisa, Nisa; Srigustini, Astri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Food diversification can be done to support the fulfillment of individual calorie and nutritional needs in order to carry out activities properly. The purpose of community service activities is that participants can understand the concepts of the Nutrient Adequacy Number (RDA) and Energy Adequacy Number (AKE), the preparation of food composition according to the recommendation of the Ministry of Health's "Isi Piringku", healthy food processing, and the use of applications to calculate calories in maintaining health. body during the Covid-19 pandemic. The method used consisted of counseling and lectures, demonstration of tools, tutorials and practice of preparing a varied and nutritionally balanced diet. PKK women from Kelurahan Ciakar who were participants in the activity were able to arrange “Isi Piringku” consisting of carbohydrate (2/3 of plate), vegetables (2/3 of plate), fruits (1/3 of plate) and side dishes (1/3 of plate). Diversification is practiced by participants using non-rice food ingredients and the use of the FatSecret application on the menu.